Implikasi Penyampingan Hukum Pidana Atas Kekerasan Dan Pembunuhan Dalam Bingkai Memorendum Of Understanding Helsinki Di Aceh - Yusi Amdani (Faculty of Law, Universitas Padjadjaran, 2018)
AbstractAceh is an Indonesian province with a long history of physical and political conflicts. The conflict in Aceh was considered as a form of human rights violation. The government have made various policies, including the establishment of the military emergency status for Aceh. The conflict had caused great loss to the people of Aceh. Fortunately, the settlement of the conflict was achieved by the signing of the Helsinki Memorandum of Understanding (MoU) for peace agreement in 2005. The establishment of the Law number 11 of 2006 concerning Aceh Governance followed the MoU. The conflicts that happened before the peace agreement, especially the ones that include criminal offenses, can be resolved through non-litigation resolution.Usually, a non-litigation resolution is used to resolve legal issues outside courtroom. The non-litigation resolution is also known as alternative settlement. The basis of the settlement is the Helsinki MoU.AbstrakAceh merupakan salah satu provinsi di Indonesia yang mempunyai sejarah pertentangan konflik dan politik yang panjang. Konflik yang terjadi di Aceh diidentifikasikan sebagai bentuk pelanggaran HAM, sehingga pemerintah membuat kebijakan penentuan status Darurat Militer untuk Aceh. Konflik tersebut menyebabkan kerugian yang besar bagi masyarakat Aceh. Namun penyelesaian konflik tersebut telah dilakukan dengan penandatanganan kesepakatan damai (MoU) Helsinki pada tahun 2005, yang kemudian dituangkan dalam UU Number 11 Tahun 2006 tentang Pemerintahan Aceh. Konflik yang terjadi sebelum kesepakatan damai, khususnya dalam bentuk tindak pidana dapat diselesaikan melalui jalur non ligitasi. Jalur non litigasi merupakan penyelesaian masalah hukum di luar pengadilan. Jalur non litigasi yang dikenal dengan Penyelesaian Alternatif. Dasar penyelesaian tersebut yaitu melalui MoU Helsinki yang merupakan ikrar perdamaian antara republik Indonesia dengan Aceh.DOI: https://doi.org/10.22304/pjih.v5n2.a7